2016
DOI: 10.1002/jmv.24650
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus epidemiology and surveillance before vaccine introduction in Argentina, 2012–2014

Abstract: Group A Rotavirus has been widely described as one of the most important infantile diarrheal pathogens worldwide. In Argentina, it is responsible for over 200,000 acute diarrhea cases and from 30 to 50 deaths annually in children under 5 years. The aim of this study is to analyze frequency, seasonality, age group distribution, and circulating genotypes based on data notified in the 2012-2014 period and in turn to assess the pre-vaccine scenario, considering that rotavirus vaccine was introduced in 2015. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Seasonal fluctuations in rotavirus infection are documented, with an increase of the viral activity in cold and dry months (6,(13)(14)(15)(16)(17). However, in accordance with other studies that describe RV as circulating throughout the year (6,18,19), in our study, the presence of RV was demonstrated during the four seasons of the 3 years sampled, with a decrease in the frequency of detection in the spring.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Seasonal fluctuations in rotavirus infection are documented, with an increase of the viral activity in cold and dry months (6,(13)(14)(15)(16)(17). However, in accordance with other studies that describe RV as circulating throughout the year (6,18,19), in our study, the presence of RV was demonstrated during the four seasons of the 3 years sampled, with a decrease in the frequency of detection in the spring.…”
Section: Discussionsupporting
confidence: 90%
“…It is estimated that RV causes more than approximately 600,000 deaths annually in children all over the world. In Argentina, it is responsible for 40% of hospital admissions of acute diarrhea, and it is estimated that this virus may cause between 30 and 50 deaths annually in the country (13).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of the Argentinean G3P[6]-2011 genes showed that despite presenting a typical Genotype 2 constellation, all of them clustered distantly from the prototype strain DS1 (G2P[4]); and more closely related to the G3P[6] and G2P[6] strains recently detected in Belgium and USA [19] [20] , respectively ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Latin America, G3P[8] has been barely detected (i.e. <0.5%) [43] [44] until recently, when >39% of the rotavirus strains circulating in Argentina during 2008–2010 presented this G and P combination [18] [19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation